Cold and Hot Extremozymes: Industrial Relevance and Current Trends - Sarmiento, Felipe; Peralta, Rocío; Blamey, Jenny M. (Frontiers in Bioengineering and Biotechnology, 2015)
The development of enzymes for industrial applications relies heavily on the use of microorganisms. The intrinsic properties of microbial enzymes e.g. consistency, reproducibility and high yields along with many others, has pushed their introduction into a wide range of products and industrial processes. Extremophilic microorganisms represent an underutilized and innovative source of novel enzymes. These microorganisms have developed unique mechanisms and molecular means to cope with extreme temperatures, acidic and basic pH, high salinity, high radiation, low water activity, and high metal concentrations among other environmental conditions. Extremophile derived enzymes, or extremozymes, are able to catalyze chemical reactions under harsh conditions, like those found in industrial processes, which were previously not thought to be conducive for enzymatic activity. Due to their optimal activity and stability under extreme conditions, extremozymes offer new catalytic alternatives for current industrial applications. These extremozymes also represent the cornerstone for the development of environmentally-friendly, efficient and sustainable industrial technologies. Many advances in industrial biocatalysis have been achieved in recent years, however, the potential of biocatalysis through the use of extremozymes is far from being fully realized. In this article, the adaptations and significance of psychrophilic, thermophilic and hyperthermophilic enzymes, and their applications in selected industrial markets will be reviewed. Also the current challenges in the development and mass-production of extremozymes as well as future prospects and trends for their biotechnological application will be discussed.